Creative Marketing Strategies to Increase MSME Telur Gulung Sales - Ningrum, Elsa Dita; Sholehah, Shoffie Ayu; Harmi, Marisa; Octaviani, Erdela; Rian, Deta; Elfemi, Nilda; Yuhelna, Yuhelna (Universitas PGRI Sumatera Barat, 2024)
This research discusses the importance of economic growth in achieving prosperity for a country through the development of Micro, Small and Medium Enterprises in the food sector, with a focus on the egg roll business. Culinary is a growing and promising industry, and eggs are a popular base in many dishes. Egg rolls are an interesting dish and have a wide variety of flavors and textures. Aje Egg Roll Trading Business, one of the business actors in this field, uses creative marketing strategies by utilizing social media such as TikTok to attract consumer attention. Determining the optimal selling price is also an important factor in this business competition. In this context, Telur Guling Aje offers variations of jumbo egg rolls that attract consumers' interest.